Topographical-anatomical justification of approaches to the deep branch of the ulnar nerve, taking into account its relationship with the deep palmar arterial arch - Biryuk , I.G.; Khmara , T.V.; Kukovska , I.L.; Zamorskyi , I.I.; Marceniak , I.V.; Savka, V.G. (Морфологія / Morphologia / Morfologìâ, 2025)
Relevance. The study and justification of the features of access to the deep branch of the ulnar nerve is of significant clinical importance, as the examined area is anatomically complex, leading to a high risk of damage to both nerve and vascular structures during surgical interventions. The study aimed to supplement and clarify the existing literature on the topography and age-related characteristics of the deep branch of the ulnar nerve and the deep palmar arterial arch. Methods. The features of the age-related topography of the deep branch of the ulnar nerve were studied on 40 specimens of the right and left hands of individuals of different ages (12 fetuses aged 4–10 months and 8 individuals in the early adulthood period), and of both sexes, using macromicroscopic dissection, vascular injections, sequential sketching of dissection stages, and morphometry. Results. This study supplements and clarifies the data on the topographical-anatomical relationships between the deep branch of the ulnar nerve, the deep palmar branch of the ulnar artery, and the deep palmar arterial arch. It was determined that the topography of the deep branch of the ulnar nerve is closely related to age. The level at which the deep branch of the ulnar nerve departs shifts proximally with age: in fetuses, it is located at the area of the hook of the hamate bone or at the level of the hook of this bone, reaching the pisiform bone in individuals of adolescent age. Conclusion. The results of the research provide the opportunity to more accurately navigate the syntopy of anatomical structures, particularly on the ulnar and radial sides of the hand. The characteristics of the relationships between the studied structures create important landmarks for surgical interventions and determine the feasibility of using the Henry approach, which minimises trauma to the vascular-nervous complex in this area.